PERSEPSI GURU SEKOLAH DASAR TERHADAP MODEL RADEC: TEMUAN STUDI PENDAHULUAN - Rosmalailaturrizqiyani; Dr. Ghullam Hamdu, M.Pd; Agnestasia Ramadhani M.Pd (STKIP Subang, 2025)
The RADEC (Read–Answer–Discuss–Explain–Create) learning model is oneapproach designed to improve the quality of 21st century learning through activestudent involvement. However, in practice, not all teachers understand thedifferences between the RADEC model and conventional learning. This study aimsto describe the perceptions of elementary school teachers towards the RADECmodel as a basis for developing learning tools. The study used a descriptivequalitative approach with data collection techniques through interviews,observations, and documentation. The subjects of the study consisted of teachersin several elementary schools who were or were not familiar with the RADECmodel. The results of the study showed that most teachers did not fully understandthe structure of the RADEC stages, and were not able to distinguish the context ofRADEC from ordinary learning. In addition, variations were found in theinterpretation and application of RADEC which were influenced by limited trainingand socialization. These findings indicate the need for ongoing training anddevelopment of learning tools, such as Student Worksheets (LKPD), which refer tothe principles of RADEC consistently and applicatively. This study provides animportant basis for designing learning development that is in accordance with theneeds of teachers in the field.